Supplementation of fermented Maillard-reactive whey protein enhances immunity by increasing NK cell activity. Issue 4 (6th April 2017) - Kang, Miso; Oh, Nam Su; Kim, Minjoo; Ahn, Hyeon Yeong; Yoo, Hye Jin; Sun, Minghan; Kang, Shin-Ho; Yang, Hye Jeong; Kwon, Dae Young; Lee, Jong Ho
Abstract : Objective : The objective of this study was to investigate the impact of supplementation with fermented Maillard-reactive whey protein (F-MRP) on natural killer (NK) cell activity, circulating cytokines, and serum protein levels. Abstract : Objective : The objective of this study was to investigate the impact of supplementation with fermented Maillard-reactive whey protein (F-MRP) on natural killer (NK) cell activity, circulating cytokines, and serum protein levels. Methods : A randomized, double-blind, placebo-controlled study was conducted on a sample of 80 participants without diabetes or obesity. Over an 8-week study period, the F-MRP group consumed 6 g of powder containing 4.2 g of F-MRP each day, whereas the placebo group consumed the same amount of maltodextrin. For each participant, NK cell activity was evaluated based on the ratio of effector cells (E; peripheral blood mononuclear cells, PBMCs) to target cells (T; K562 cells) at E : T ratios of 10 : 1, 5 : 1, 2.5 : 1, and 1.25 : 1. Results : Body mass index (BMI) and NK cell activity under all assay conditions were significantly increased in the F-MRP group at the 8-week follow-up visit compared with the values at the baseline, whereas the placebo group showed significant reductions in NK cell activity (at an E : T ratio of 5 : 1), serum albumin, and pre-albumin at the 8-week follow-up visit compared with the values at the baseline. When comparing the changes between the placebo and F-MRP groups, the increases in NK cell activity under all assay conditions and serum interleukin (IL)-12 in the F-MRP group were greater than those in the placebo group after adjusting for baseline values. There were also significant differences in pre-albumin and insulin-like growth factor (IGF)-1 between the two groups; the change in (Δ) IL-12 was positively correlated with both Δpre-albumin ( r = 0.435, P = 0.006) and ΔNK cell activity at an E : T ratio of 10 : 1 ( r = 0.571, P < 0.001) in the F-MRP group. Conclusion : Daily consumption of F-MRP enhanced NK cell function, which was positively associated with ΔIL-12. Moreover, ΔIL-12 was positively correlated with Δpre-albumin.